1987
DOI: 10.1021/jm00395a015
|View full text |Cite
|
Sign up to set email alerts
|

2-Oxo-1,8-naphthyridine-3-carboxylic acid derivatives with potent gastric antisecretory properties

Abstract: The syntheses of 2-oxo-1,8-naphthyridine-3-carboxylic acid derivatives having potent gastric antisecretory properties in the pyloric-ligated (Shay) rat model are described. Two of the more potent compounds tested that were selected for more detailed dose-response evaluation were 4-amino-1-ethyl-1,2-dihydro-2-oxonaphthyridine-3-carboxylic acid ethyl ester (35) and 1-ethyl-1,2-dihydro-7-methyl-4-(4-methyl-1-piperazinyl)-2- oxo-1,8-naphthyridine-3-carboxylic acid ethyl ester (77). These compounds lowered total ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0
2

Year Published

1988
1988
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(34 citation statements)
references
References 1 publication
0
32
0
2
Order By: Relevance
“…These compounds were evaluated by Santilli et al [169] in the pyloric-ligated (Shay) rat model. Active compounds were 4-amino-1-ethyl-1,2-dihydro-2-oxonaphthyridine-3-carboxylic acid ethyl ester (105) and 1-ethyl-1,2-dihydro-7-methyl-4-(4-methyl-1-piperazinyl)-2-oxo-1,8-naphthyridine-3-carboxylic acid ethyl ester, which lowered total acid output in the rat in a dose-related fashion.…”
Section: Antimalarial Propertiesmentioning
confidence: 99%
“…These compounds were evaluated by Santilli et al [169] in the pyloric-ligated (Shay) rat model. Active compounds were 4-amino-1-ethyl-1,2-dihydro-2-oxonaphthyridine-3-carboxylic acid ethyl ester (105) and 1-ethyl-1,2-dihydro-7-methyl-4-(4-methyl-1-piperazinyl)-2-oxo-1,8-naphthyridine-3-carboxylic acid ethyl ester, which lowered total acid output in the rat in a dose-related fashion.…”
Section: Antimalarial Propertiesmentioning
confidence: 99%
“…The first naphthyridine derivatives were prepared in 1893 by Reissert who suggested the name naphthyridine [5]. From literature it was also noted that 1,8-naphthyridine derivatives were not only use as luminescence materials in molecular recognition because of their rigid planer structure [6][7][8], possess antibacterial [9], antymicobacterial [10], antitumoral [11], anti-inflammatory [12], antiplatelet [13], gastric antisecretary [14], antiallergic [15] and local anaesthetic [16]. Recently, our research group reported systematic studies about the fluorescence properties of differently substituted pyrazolofused heterocycles [17][18][19][20][21][22] and benzo naphthyridines [23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…A survey of the literature shows that the major synthetic approaches that are used to prepare various types of 1,8-naphthyridine system involves condensation of 2-aminopyridine derivatives with carbonyl compounds containing an activated methylene group [10][11][12][13][14][15][16] or with β-ketoesters [17]. Another general procedure for the preparation of 1,8-naphthyridine condensed ethanolic 2-amino-3-formylpyridines, in the presence piperidine base, with active methylene compounds, aldehydes, acyclic and cyclic ketones or diketones [18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%